Penerapan E-modul anthropogenic climate change untuk meningkatkan keterampilan berpikir Kreatif - Musdalifa; Darsikin; Unggul Wahyono; Sitti Rahmawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an e-module on anthropogenic climate change to enhance students' creative thinking skills. This research is a Research and Development (R&D), using the ADDIE development model. The research was conducted at MAN Tolitoli, taking 28 students each from the experimental class and the control class as comparators in this study. The results of the Cohen's effect size analysis yielded 0.48, categorised as medium, and there was also a significant increase in creative thinking skills in the experimental class, which improved from the category of fairly skilled to skilled and even very skilled in each session. Additionally, there was an improvement in the posttest results of the students in the experimental class.